Limit Theorems for Random Elements in Ideals of Order-Bounded Elements of Functional Banach Lattices - Matsak, I. K.; Plichko, A. M. (Ukrains’kyi Matematychnyi Zhurnal, 2001)
For a sequence of independent random elements belonging to an ideal of order-bounded elements of a Banach lattice, we investigate the asymptotic relative stability of extremal values, the law of large numbers for the pth powers, and the central limit theorem.